A educação física no contexto de modernização educacional em Goiás (1929-1937) - (:unkn) unknown (Universidade Federal de Goiás, 2018)
The present research is about physical education in the context of educational modernization in Goiás. Its objective is to analyze the participation of physical education in the modernization of education in Goiás, from 1929-1937. And as specific objectives, to raise aspects of modernization in Goiás; to discuss the fundamentals of physical education in the context of educational modernization in Goiás; to present the narratives about physical education transmitted in Goiás during the period 1929-1937. It is a historical narrative subsidized by the documentary corpus: Correio Official newspaper of the State of Goyas; magazine A informação Goyana; report of the governor Pedro Ludovico Teixeira to the president of the republic Getúlio Vargas (1930-1933); educational laws and decrees related to physical education that were in force in Goiás in the period referring to the research cut; documents of the Fundo Lyceu de Goyas in the Museu das Bandeiras. The theoretical references of support, in what concerns the modernization and the educational modernization in Goiás, were Bretas (1991), Silva (1975), Borges (1990), Nepomuceno (1994), Pinto (2009), Chaul (2010). As for physical education were Dias (2013, 2014), Soares (2004, 1998), Paiva (2004), Parada (2006), Schneider e Ferreira Netto (2008), among others. Among the results, it is highlighted that, through distinct contents, that is, gymnastics, popular games, sports games and sports, physical education participated in the modernization of education and the city through an education of the body that contradictorily sought control and liberty.
Physical education in the context of educational modernization in Goiás (1929-1937)
Keywords: Educação física; Modernização educacional em Goiás; Modernização; Educational modernization in Goiás; Physical education; Modernization; EDUCACAO::CURRICULO